2021
DOI: 10.1017/s1368980021000628
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019, food security and maternal mental health in Ceará, Brazil: a repeated cross-sectional survey

Abstract: Objective To quantify the change in the risk of food insecurity and maternal mental disorder (MMD) before and during the COVID-19 pandemic. Design Repeated cross-sectional survey. Between July 17 and September 10, 2020, mother-child pairs who were enrolled in a population-based survey in 2017 were re-contacted by telephone for consent and to complete a telephonic COVID-19 survey. We used the Brazilian Food Insecurity Scale to assess food security and the Self Reporting Questionnaire (SRQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
10
1
2
Order By: Relevance
“…The same rate was 45%, according to Kundu et al [29], while Hamadani et al [30] reported a 43% increase in Bangladesh. In Brazil, according to Rocha et al [31], the prevalence of food insecurity among mothers was 15% higher between July and September 2020 than it was in 2017.…”
Section: Time and Place Of Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same rate was 45%, according to Kundu et al [29], while Hamadani et al [30] reported a 43% increase in Bangladesh. In Brazil, according to Rocha et al [31], the prevalence of food insecurity among mothers was 15% higher between July and September 2020 than it was in 2017.…”
Section: Time and Place Of Collectionmentioning
confidence: 98%
“…In some cases, in addition to the partial or total income loss, households even had to face rising food prices [20,38]. In order to mitigate income-loss-related food insecurity of households, the most common strategy was launching food or financial benefit programs, mostly by governmental organizations [31,33,39,40], but there were examples of households taking loans or borrowing cash from formal or informal sources [38,39]. Ibrahim and Othman provided information from Malaysia about a third kind of strategy, where 32% of the respondents started to pick vegetables from the area around their house and 27% conducted online business [38].…”
Section: Time and Place Of Collectionmentioning
confidence: 99%
“…Furthermore, evidence indicates that the pandemic has increased the proportion of households with moderate or severe food insecurity in LMICs, mainly through loss of income. Household food insecurity can potentially lead to increases in different forms of malnutrition (Rocha et al, 2021 ), such as iron or other micronutrient deficiencies, as well as overweight and obesity or other nutrition‐related noncommunicable diseases, which in turn increases the risk of COVID‐19 morbidity and mortality (Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Fortaleza, we showed that over three-quarters of families had their income reduced during the pandemic, which could have resulted in dietary restrictions. Indeed, food insecurity in the state of Ceará increased by 15% during the COVID-19 pandemic (Rocha et al, 2021). Therefore, food insecurity may have overcome the eventual fear of disease transmission through human milk and influenced participants to postpone the introduction of solid foods into their infant’s diet.…”
Section: Discussionmentioning
confidence: 99%